PENGARUH MODEL PEMBELAJARAN MAKE A MATCH DAN TALKING STICK TERHADAP HASIL BELAJAR SISWA TEMA 4 SUBTEMA 2 KELAS III SD - Saragih, Sri Pebriani; Lubis, Wildansyah; Nurmayani, Nurmayani; Simanungkalit, Erlinda; Purnomo, Try Wahyu (Universitas Negeri Medan, 2024)
The problem is this study is the low learning outcomes of class III students at SD Negeri 101764 Bandar Klippa T.A 2023/2024. This study aims to determine the effect of student learning outcomes with the use of learning model Make A Match dan Talking Stick on Theme 4 Sub-theme 2 Obligations and Rights. Class III SD Negeri 101764 Bandar Klippa Academic Year 2023/2024. Location The research was conducted at SD Negeri 101764 Bandar Klippa, which consisted of 2 classes, namely: Class IIIA (Experimental Class 1) and Class IIIB (Experimental Class 2). Class IIIA with a total of 20 students and class IIIB with a total of 21 students. The sample collection technique with Total Sampling is the selection of a sample where the entire population is selected as a sample. This type of research is a quasi-experimental research design with Non Equivalent Multiple Group Design and quantitative data. The data collection tool used to determine student learning outcomes is an objective test with a total of 20 questions that have been tested for validation and reliability. From the data analysis with a sample of 20 students in experimental class 1 and 21 students in experimental class 2, it was obtained that the average of experimental class 1 was at Pre-Test 49,5 and Post-Test 81 while in experimental class 2 at Pre-Test 51,9 and Post-Test 78,57. At a significant level Both classes are normally distributed because is (experimental class 1) and (experimental class 2). Homogenity test in the Post-Test experimental class 1 and experimental class 2 with, namely The t-test was carried out at the significant level that is The writer concludes that there is a significant effect of Make A Match and Talking Stick learning model on theme 4 Sub-theme 2 Obligations and Rights. Class III SD Negeri 101764 Bandar Klippa Academic Year 2023/2024.